The electrification of energy: Long-term trends and opportunities. (5th June 2018) - Tsao, Jeffrey Y.; Schubert, E. Fred; Fouquet, Roger; Lave, Matthew
ABSTRACT: Abstract : We present and analyze three powerful long-term historical trends in the electrification of energy by free-fuel sources. These trends point toward a future in which energy is affordable, abundant, and efficiently deployed; with major economic, geo-political, and environmental benefits to humanity. We present and analyze three powerful long-term historical trends in energy, particularly electrical energy, as well as the opportunities and challenges associated with these trends. The first trend is from a world containing a diversity of energy currencies to one whose predominant currency is electricity, driven by electricity's transportability, exchangeability, and steadily decreasing cost. The second trend is from electricity generated from a diversity of sources to electricity generated predominantly by free-fuel sources, driven by their steadily decreasing cost and long-term abundance. These trends necessitate a just-emerging third trend: from a grid in which electricity is transported unidirectionally, traded at near-static prices, and consumed under direct human control; to a grid in which electricity is transported bidirectionally, traded at dynamic prices, and consumed under human-tailored artificial agential control. These trends point toward a future in which energy is not costly, scarce, or inefficiently deployed but instead is affordable, abundant, and efficiently deployed; with major economic, geo-political, and environmental benefits to humanity.